Educational Tools for Early Childhood and Creativity in Attribute and Organisation Perspective (Indonesian Journal of Early Childhood Education Studies, 2022)
This article attempts to illustrate the development of creativity and educative gaming tools when reviewed from the perspective of attributes and organizations. The methodology used is Library Research by searching for data through books, journal artifacts and documentation. The results of this writing know that in order to develop creativity in the perspective of the attribute, it is thought that in creativity teachers have the ability of flexible thinking and the results of their own thoughts. The creation of a game tool educative perspective attribute has three important elements namely attention to quality, features and product design. Judging from the quality, educative game tools should work as per its function, while the features of the educational game tools must have different characteristic or characteristic than before, and the design of educational game tools must have a form, feature, comfort, safety, reliability and interesting style. While creativity in the perspective of the organization asks teachers to be careful, analysis, innovative, focus on the needs of children, can be used in groups (cooperative), and consistently determine the decision. Then an educative game tool in the organizational perspective must have seven dimensions namely bold at risk, detail, individual orientation, team orientation, aggressive, and stability. Keywords: Creativity; Educative game tools; Attribute Organization